Evolution of potential evapotranspiration in the northern Loess Plateau of China: recent trends and climatic drivers. (25th January 2016) - Ning, Tingting; Li, Zhi; Liu, Wenzhao; Han, Xiaoyang
ABSTRACT: Potential evapotranspiration represents the maximum evaporative capacity for a region, which underscores the importance of analysing its changes and attribution to provide information for water resource management. This study focused on the northern Loess Plateau of China, investigated the changes in potential evapotranspiration (ET0 ) using data from 34 stations during 1960–2013 and conducted its temporal and spatial attribution through the differentiation equation method. The results show that the annual mean ET0 is 1004.9 mm with a decreasing trend at the rate of 0.33 mm year −1 . The lowest values were found in the northeast and southwest regions, while the greatest ET0 was in the northwest region. An 'evaporation paradox' existed as a whole, but not obviously. The ET0 was most sensitive to actual vapour pressure ( e a ), followed by solar radiation ( R s ), mean temperature ( T mean ) and wind speed ( U 2 ). The inter‐annual variation in the sensitivity of ET0 in relation to climatic factors showed that ET0 became more sensitive to U 2 and T mean but less sensitive to R s and e a from 1960 to 2013. Temporally, the increasing T mean resulted in the increase of ET0 ; while its effect was weakened by the other three factors, especially by decreasing U 2 . The contributions of climatic factors to the ET0 spatial variation trends were also analysed along two transects, but the dominant factors were different for each transect. Furthermore, the possible impacts of human activities on ET0 changes were also discussed.